Coastal drowning deaths in Australia: Is a 50% reduction by 2020 within reach?. (7th October 2012) - Sherker, Shauna; Brighton, Barbara; Thompson, Matt
Abstract : Objective: To describe coastal drowning death in Australia and to assess compliance with the Australian Water Safety Strategy (AWSS) drowning reduction targets. Design: A retrospective epidemiological review of all coastal drowning deaths in Australia from 1 July 2004 and 30 June 2011. Data was collected from the National Coroners Information System, Surf Life Saving Australia Incident Report Database (SurfGuard) and Media Monitors. Drowning projections to 2020 were estimated and tested against AWSS drowning reduction targets. Results: The number of coastal drowning deaths in Australia from 2004–2011 was 625, or on average 89 deaths per year. The average annual drowning rate was 0.42 per 100 000 population . Most deaths were male (85.1%) and aged 20–39 years (36.4%). Most occurred in NSW (40.6%), Queensland (15.9%) and Victoria (14.8%). Common activities undertaken at the time of drowning were swimming/wading (34.1%), boating (17.6%) and rock fishing (12.4%). Of the swimming/wading related drowning, 42% involved a rip current. The projected coastal drowning rate for 2020 is 0.27 per 100 000 pop., which is a 44% reduction from the baseline coastal drowning rate of 0.48 per 100 000 pop. Conclusions: In Australia, coastal drowning deaths are over-represented in swimming/wading, boating, and rock fishing activities. If the current trend continues, the AWSS goal of a 50% reduction in coastal drowning deaths by 2020 will not be achieved. Efforts in coastal drowning prevention must be increased. A strong focus on providing quality lifesaving services and promoting a safe coastal aquatic environment is warranted. Public education regarding rip currents, boating and fishing safety is essential.